Color Doppler imaging features in patients presenting central retinal artery occlusion with and without giant cell arteritis - Jianu, Dragos Catalin; Jianu, Silviana Nina; Munteanu, Mihnea; Vlad, Daliborca; Rosca, Cosmin; Petrica, Ligia (Vojnosanitetski pregled, 2017)
Introduction. Central retinal artery obstruction (CRAO) represents an abrupt diminution of blood flow through the CRA that is severe enough to cause ischemia of the inner retina with permanent unilateral visual loss. We presented the role of color Doppler imaging (CDI) of orbital vessels and of extracranial duplex sonography (EDS) in the etiological diagnosis of CRAO in two patients with clinical suspicion of unilateral CRAO. Case report. Patients were examined following the protocol which included CDI of orbital vessels and EDS. Both patients had no emboli visible on ophthalmoscopy. The B-scan ultrasound evaluation of the first patient found a small round, moderately reflective echo within the right optic nerve, 1.5 mm behind the optic disc (emboli of cholesterol). CDI of retrobulbar vessels revealed the normal right ophthalmic artery (OA) hemodynamic parameters, but the first patient had no arterial flow signal on CDI at the distance of 1.5 mm behind the right optic disc. In contrast, the left eye had the normal aspect on CDI of retrobulbar vessels. The right internal carotid artery EDS identified a severe stenosis at its origin as CRA’s emboli source. The second patient had characteristic CDI findings for giant cell arteritis (GCA) with eye involvement: severe diminished blood flow velocities, especially end-diastolic velocities, in both CRAs. Less abnormalities were observed in the posterior ciliary arteries, and in the ophthalmic arteries. The second patient had no systemic symptoms or signs of GCA. Conclusion. In the presented cases, the ultrasound investigation enabled prompt differentiation between central retinal artery occlusion of embolic mechanism and CRAO caused by GCA.
Keywords: retinal artery occlusion; ultrasonography; doppler; color; giant cell arteritis; diagnosis; differential